Analysis of the idioms of (head) in Kurdish language, from the perspective of cognitive linguistics (Raparin Journal of Humanities (RJH), 2024)
This study is entitled (Analysis of the idioms of (head) in Kurdish language, from the perspective of cognitive linguistics). Language is one of the most important human achievements and occupies a large space in human life. Therefore, since the ancient times, humans have paid attention to it and tried to understand its secrets.Idioms are an important part of any language, and studying them helps us to understand the relationship between idioms and metaphors. The school of cognitive linguistics looks at idioms differently from all other linguistic schools. Other linguistic schools have studied the syntactic, semantic and pragmatic aspects of idioms and viewed them as fixed and inseparable structures and expressions. However, the cognitive linguists have a completely different view; they see idioms as conceptual metaphors and interpret every conceptual metaphor in terms of the conceptual matching and interaction between the source and target fields.Our study is an interpretation of the idioms of (head) from the school of cognitive linguistics’ perspective, in light of the theory of conceptual metaphor, the interpretation of idioms has been conducted. In general, the study consists of the introduction, two chapters, the results and the list of references. The first chapter discusses the perception of both schools of ancient and cognitive linguistics for idioms as well as the theory of conceptual metaphor, types of conceptual metaphors and metaphorical interaction between the source and target fields. In the second chapter, the idioms of (head) have been analyzed according to the theory of conceptual metaphor, followed by the results and a list of references.